Visceral Leishmaniasis Turning into Chronic Liver Disease - Mukerrama, Shegufta Mishket; Kabir, Ahmedul; Deb, Sudip Ranjan; Dhruba, Avishek Sarker; Hasan, Pratyay; Hossain, Anwar; Hossain, Mahbub (Journal of Medicine, 2016)
Kala-azar and chronic liver disease are conditions frequently seen in our country. In some instances, when features of both diseases co-exist, it may pose as a diagnostic dilemma. We intend to report a case here, where presence of such features led to much confusion. J MEDICINE January 2016; 17 (1) : 51-54